The Effect of Current Ratio, Total Asset Turnover and Debt to Equity Ratio on Financial Distress (A Study of Textile and Garment Companies Listed on the Indonesia Stock Exchange in 2024) - Ajeng Elsa Herlina; Abdul Hafiz Tanjung (Journal of Governance, Taxation and Auditing, 2026)
This study was conducted on banking companies registered with BELI in 2024. The purpose of this study was to determine the influence of the Current Ratio, Total Asset Turnover, and Debt to Equity Ratio on Financial Distress, both partially and simultaneously. This study was conducted based on the phenomenon of companies experiencing losses due to liabilities exceeding company assets, resulting in the company potentially experiencing bankruptcy. The model used in this study is a quantitative model. The population of this study was 17 textile and garment companies registered with BELI in 2024. The sampling technique used purposive sampling technique, with 17 textile and garment companies selected. The data analysis method used was descriptive and associative analysis using logistic regression analysis, and the data processing tool used in this study was SPSS version 23. The results of this study indicate that there is a partial and simultaneous influence on the Financial Distress variable in textile and garment companies registered with BELI in 2024.